Skilled Nursing Facility Participation in a Voluntary Medicare Bundled Payment Program: Association With Facility Financial Performance. Issue 1 (January 2022) - Ying, Meiling; Temkin-Greener, Helena; Thirukumaran, Caroline P.; Joynt Maddox, Karen E.; Holloway, Robert G.; Li, Yue
Abstract : Importance: Model 3 of the Bundled Payments for Care Improvement (BPCI) is an alternative payment model in which an entity takes accountability for the episode costs. It is unclear how BPCI affected the overall skilled nursing facility (SNF) financial performance and the differences between facilities with differing racial/ethnic and socioeconomic status (SES) composition of the residents. Objective: The objective of this study was to determine associations between BPCI participation and SNF finances and across-facility differences in SNF financial performance. Design, Setting, and Participants: A longitudinal study spanning 2010–2017, based on difference-in-differences analyses for 575 persistent-participation SNFs, 496 dropout SNFs, and 13, 630 eligible nonparticipating SNFs. Main Outcome Measures: Inflation-adjusted operating expenses, revenues, profit, and profit margin. Results: BPCI was associated with reductions of $0.63 million in operating expenses and $0.57 million in operating revenues for the persistent-participation group but had no impact on the dropout group compared with nonparticipating SNFs. Among persistent-participation SNFs, the BPCI-related declines were $0.74 million in operating expenses and $0.52 million in operating revenues for majority-serving SNFs; and $1.33 and $0.82 million in operating expenses and revenues, respectively, for non–Medicaid-dependent SNFs. The between-facility SES gaps in operating expenses were reduced (differential difference-in-differences estimate=$1.09 million). Among dropout SNFs, BPCI showed mixed effects on across-facility SES and racial/ethnic differences in operating expenses and revenues. The BPCI program showed no effect on operating profit measures. Conclusions: BPCI led to reduced operating expenses and revenues for SNFs that participated and remained in the program but had no effect on operating profit indicators and mixed effects on SES and racial/ethnic differences across SNFs. Abstract : Supplemental Digital Content is available in the text.